Pyrite-coated WS2 heterogeneous Fenton composite catalyst as well as preparation method and application thereof

The pyrite @WS2 composite catalyst prepared by mechanochemical ball milling technology solves the recycling and reuse problems of traditional Fenton catalysts when treating high concentrations of organic pollutants, significantly improves the catalytic efficiency and stability, and achieves efficient, economical and environmentally friendly wastewater treatment effects.

CN119500191APending Publication Date: 2025-02-25GUANGXI UNIV FOR NATITIES +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411655808.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the existing Fenton catalysts treat high concentration, difficult to degrade and highly toxic organic pollutants, the problems of catalyst recycling and reuse and high treatment costs have not been effectively solved.

Method used

Using mechanochemical ball milling technology, nano WS2 and pretreated pyrite were ball milled to prepare pyrite @WS2 heterogeneous Fenton composite catalyst. By accurately controlling the preparation conditions of the catalyst and the concentration and pH of pollutants, the catalytic efficiency and stability of the catalyst are improved.

Benefits of technology

The catalytic performance of the catalyst was significantly improved. After five consecutive cycles of reactions, the removal rate of the model pollutant rhodamine B was still maintained above 95%, reducing secondary pollution, and showing excellent performance in the degradation of various organic dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500191A_ABST
    Figure CN119500191A_ABST
Patent Text Reader

Abstract

The invention provides a pyrite-coated WS2 heterogeneous Fenton composite catalyst as well as a preparation method and application thereof, and belongs to the technical field of organic dye sewage treatment. The method comprises the following steps: carrying out mechanochemical ball milling on nano WS2 and pretreated pyrite to prepare pyrite coated WS2; wherein the mechanochemical ball milling technology can improve the industrial wastewater treatment efficiency and reduce secondary pollution. By controlling the contrast, pollutant concentration and pH value of the catalyst, the prepared composite catalyst shows excellent catalytic activity and stability. The invention provides an effective strategy for solving the self-repairing and recycling problems of the traditional Fenton catalyst in practical application, is expected to be widely applied to the field of industrial wastewater treatment, and promotes the development of an environment treatment technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic dye wastewater treatment, and in particular relates to a pyrite@WS2 heterogeneous Fenton composite catalyst and a preparation method and application thereof. Background Art

[0002] In the context of the current acceleration of the global industrialization process, the wastewater problem caused by industrial production has become increasingly prominent, posing a severe challenge to the sustainability of the environment and energy. For a long time, the treatment of high-concentration, toxic and poorly degradable organic pollutants, especially printing and dyeing wastewater, has been a major challenge in the field of wastewater treatment. At present, the mainstream methods for dye wastewater treatment include aerobic biological treatment, membrane separation, Fenton catalysis, etc. However, in practical applications, the emission standards after aerobic biological treatment are difficult to achieve, and one limitation of the membrane separation method is that when treating high-concentration dye wastewater, the permeable membrane is easily contaminated and blocked. In contrast, Fenton catalytic technology has significant advantages in treating high-concentration, difficult to degrade and highly toxic organic pollutants. It produces strongly oxidizing hydroxyl radicals, which can effectively degrade organic pollutants in wastewater without causing secondary pollution. However, Fenton technology also has some limitations, such as the recovery and reuse of catalysts, and high treatment costs, which need to be solved urgently.

[0003] Pyrite is widely distributed in nature (Wilkin et al., 1996; Chandra and Gerson, 2010), with abundant reserves (Rickard and Luther, 2007), and is environmentally compatible. It is one of the most abundant iron minerals in the earth's crust. China ranks first in the world in terms of pyrite reserves and mining volume. Its application prospects in the field of environmental protection, especially as a barrier material or emergency treatment material, are receiving more and more attention. The main active component of natural pyrite is ferrous disulfide (FeS2), which is regarded as a potential multiphase Fenton reagent. Yu et al. used a hydrothermal method to synthesize pyrite as a multiphase Fenton catalyst to study its degradation of mycophenolic acid (DCF). Under non-electric conditions, 50 mg / L DCF was catalyzed by 0.8 g pyrite in 100 mL, and the degradation rate reached 90% in 90 minutes, and it was completely degraded in 5 minutes after power was turned on. However, it is worth noting that the low efficiency of FeS2-based catalytic systems in promoting the decomposition of recalcitrant organic matter and problems such as iron ion spillover have not been fundamentally solved.

[0004] Therefore, improving the catalytic efficiency of pyrite-based catalysts and solving the problem of iron ion spillover have far-reaching economic and environmental significance for achieving environmental sustainability. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a pyrite @ WS2 heterogeneous Fenton composite catalyst and its preparation method and application; the present invention uses natural pyrite as the iron source material and WS2 as the co-catalyst, and successfully prepares a new type of heterogeneous Fenton reagent pyrite @ WS2 through mechanochemical ball milling technology. Compared with the degradation ability of pure pyrite and nano WS2 after separate pretreatment, the catalytic performance of the pyrite @ WS2 composite catalyst prepared by the present invention is greatly improved. Finally, the present invention deeply studies the main active components in the degradation reaction and evaluates the versatility and cyclic degradation ability of the composite catalyst under different conditions. That is, the present invention provides a new perspective for the research of multiphase Fenton catalytic technology and its application in the field of environmental remediation; it is expected to promote the development of efficient, economical and environmentally friendly wastewater treatment technology, and provide new solutions to solve increasingly severe environmental problems.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst comprises the following steps:

[0009] Nano-WS2 and pre-treated pyrite were subjected to mechanochemical ball milling to prepare pyrite@WS2 (denoted as Pyrite@WS2);

[0010] Wherein, the mass ratio of the pretreated pyrite to the nano WS2 is (1-10) : 1. Preferably, the mass ratio of the pretreated pyrite to the nano WS2 is 1:1, 5:1, 7:1 or 10:1.

[0011] Beneficial effects: In the composite catalyst prepared by the present invention, the introduction of nano-WS2 can effectively promote the cyclic conversion between ferric ions and ferrous ions, significantly reduce secondary pollution, and the free radical capture experiment proves that its main active substance is ·OH. According to the effect of degrading rhodamine B recorded in the present invention, after 5 consecutive cycles of reaction, the removal rate of the composite catalyst for the model pollutant rhodamine B can be continuously maintained at more than 95%, and the composite catalyst shows excellent performance in the degradation of various organic dyes;

[0012] In addition, the mechanochemical ball milling method disclosed in the present invention has simple steps, mature technology, and is suitable for large-scale promotion. The composite catalyst disclosed in the present invention and its preparation method provide an effective strategy for solving the self-repair and recovery problems faced by traditional Fenton catalysts in practical applications, and are expected to be widely used in the field of industrial wastewater treatment and promote the development of environmental governance technology.

[0013] Furthermore, the mass ratio of the pretreated pyrite to the nano-WS2 is 7:1.

[0014] Preferably, the ball milling speed during the mechanochemical ball milling process is 300 to 500 rpm, preferably 400 rpm; the ball milling time is 24 to 48 h, preferably 48 h.

[0015] Furthermore, the material ratio of zirconium oxide grinding balls during the mechanochemical ball milling process is 10-50, preferably 30.

[0016] Preferably, the preparation process of the nano WS2 is:

[0017] Dissolve Na2WO4·2H2O, NH2OH·HCl and CH4N2S in water to obtain a mixed solution;

[0018] The mixed solution is first heated at a constant temperature and then cooled to room temperature.

[0019] Furthermore, the mixed solution needs to be adjusted to a pH of 6.0 using hydrochloric acid; the concentration of the hydrochloric acid is 1.5 mol / L-2.5 mol / L, preferably 2 mol / L.

[0020] Furthermore, the usage ratio of Na2WO4·2H2O, NH2OH·HCl, CH4N2S and water is: (1.5-1.7) g: (0.6-0.7) g: (1.4-1.6) g: 30 mL.

[0021] Furthermore, the heating temperature in the constant temperature heating process is 180° C. and the heating time is 24 hours.

[0022] Furthermore, after cooling to room temperature, the precipitate needs to be taken out, washed and dried;

[0023] The conditions in the drying process are: drying at 60° C. and vacuum conditions for 10 hours.

[0024] Preferably, the operation of the pretreated pyrite is: washing the pyrite three times and drying it at 70° C. under vacuum for 12 hours.

[0025] The second technical solution of the present invention:

[0026] A pyrite@WS2 heterogeneous Fenton composite catalyst is prepared according to the above preparation method.

[0027] The third technical solution of the present invention:

[0028] The above-mentioned pyrite@WS2 heterogeneous Fenton composite catalyst is used for catalytic degradation of organic dye pollutants in wastewater, wherein the organic dye pollutants include methylene blue, methyl orange, rhodamine B or a mixture of the three; the mass ratio of methylene blue, methyl orange and rhodamine B in the mixed pollutants is 1:1:1.

[0029] Preferably, H2O2 needs to be added during the catalytic degradation of organic dye pollutants in water.

[0030] Furthermore, the concentration of organic dye pollutants in the sewage is 10-30 mg / L; the pH of the sewage is 2.00-6.00; and the concentration of the H2O2 solution is 4.5 mmol / L.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The present invention proposes for the first time a method for preparing a novel heterogeneous Fenton reagent pyrite @WS2. The method adopts mechanochemical ball milling technology, aiming to improve the efficiency of industrial wastewater treatment and significantly reduce secondary pollution. By precisely controlling the preparation conditions of the catalyst, the concentration of pollutants, and the pH value, efficient degradation of organic pollutants is achieved. That is, the composite catalyst prepared by the present invention exhibits excellent catalytic activity and stability. Among them, the introduction of nano WS2 can effectively promote the conversion between iron ions and ferrous ions, effectively reducing secondary pollution. Through free radical capture experiments, it is confirmed that its main active substance is ·OH free radicals. After 5 consecutive cycles of reaction, the removal efficiency of the model pollutant Rhodamine B by the system can still be maintained at more than 95%. In addition, the composite catalyst also exhibits excellent performance in the degradation of a variety of organic dyes (such as methylene blue, methyl orange, Rhodamine B and mixed pollutants).

[0033] The invention also discloses a method for preparing the composite catalyst, which has simple process, mature technology and is very suitable for large-scale production. The invention also provides an effective solution strategy for the self-repair and recycling problems of traditional Fenton catalysts in practical applications, and is expected to be widely used in the field of industrial wastewater treatment and promote the advancement of environmental governance technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1 This is a process flow chart for preparing a heterogeneous Fenton pyrite-based composite WS2 catalyst of the present invention;

[0036] Figure 2This is an actual sample picture of Pyrite@WS2 prepared under the condition of pre-treated Pyrite: nano WS2=7:1 in Example 1 of the present invention;

[0037] Figure 3 The SEM images of Pyrite@WS2 and pretreated Pyrite prepared under the condition of pretreated Pyrite: nano WS2=7:1 in Example 1 of the present invention;

[0038] Among them, a is the pre-treated Pyrite; b is the Pyrite@WS2 at 20nm scale; c is the Pyrite@WS2 at 200nm scale;

[0039] Figure 4 XRD diagrams of Pyrite@WS2 and pretreated Pyrite prepared under the condition of pretreated Pyrite: nano WS2 = 7:1 in Example 1 of the present invention;

[0040] Figure 5 This is a diagram showing the degradation effects of Pyrite@WS2 prepared in Example 1 of the present invention, and the pretreated Pyrite, nano WS2, and H2O2 on RhB;

[0041] Figure 6 The figure is a graph showing the degradation effect of Pyrite@WS2 prepared under the condition of pre-treated Pyrite: nano WS2 = 7:1 on RhB under different RhB concentrations in Example 1 of the present invention;

[0042] Figure 7 The degradation effect of Pyrite@WS2 on RhB prepared under the condition of pre-treated Pyrite: nano WS2 = 7:1 in Example 1 of the present invention at different pH values;

[0043] Figure 8 Schematic diagram of the cyclic degradation times of the composite catalyst Pyrite@WS2 (7:1) prepared in Example 1 under the conditions of Rhb concentration of 20 mg / L and RhB pH of 4;

[0044] Fig. 9 This is a schematic diagram of the degradation of methylene blue, methyl orange, rhodamine B and mixed pollutants by Pyrite@WS2 prepared under the condition of pretreated Pyrite: nano WS2 = 7:1 in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0050] The present invention provides a method for preparing a Pyrite@WS2 self-repairing cyclic catalyst, and the specific steps are as follows:

[0051] (1) The pyrite is simply ground, sieved, washed, and placed in a vacuum drying oven for drying pretreatment;

[0052] (2) Preparation of nano WS2:

[0053] First, weigh Na2WO4·2H2O, NH2OH·HCl, and CH4N2S, dissolve them in water, mix and stir, and add HCl to adjust the pH;

[0054] Secondly, the mixed solution is added into the autoclave, moved to an electric constant temperature blast drying oven for heating, and cooled naturally to room temperature;

[0055] Finally, the precipitate was taken out, washed with deionized water and anhydrous ethanol, transferred to a watch glass, dried in a vacuum drying oven, and then taken out for storage;

[0056] (3) weighing the pretreated pyrite and nano-WS2 and mixing them in a certain mass ratio to obtain a mixture;

[0057] (4) The mixture was added into a 100 mL zirconia ball mill jar, and after adding zirconia grinding balls, the mixture was placed in a ball mill for dry grinding to obtain a pyrite@WS2 composite catalyst.

[0058] In some preferred embodiments, the mesh size of the sieve in step (1) is set at 300 mesh.

[0059] In some preferred embodiments, the washing in step (1) is first rinsed with deionized water and then dehydrated with anhydrous ethanol, which is repeated 3 times. The drying is performed under vacuum at a temperature of 70° C. for 12 hours.

[0060] In some preferred embodiments, in step (2), 1.6493 g Na2WO4·2H2O, 0.6949 g NH2OH·HCl and 1.5224 g CH4N2S are accurately weighed and dissolved in 30 mL deionized water.

[0061] In some preferred embodiments, the concentration of HCl in step (2) is 2 mol / L, and the pH is adjusted to 6.

[0062] In some preferred embodiments, the heating temperature in step (2) is set at 180° C. and the heating time is 24 h.

[0063] In some preferred embodiments, the precipitate in step (2) is placed in a centrifuge tube and centrifuged and washed 10 times with water and 10 times with alcohol.

[0064] In some preferred embodiments, the drying temperature in step (2) is 60° C., the drying condition is vacuum, and the drying time is 10 h.

[0065] In some preferred embodiments, the mass ratio of pyrite and nano-WS2 after pretreatment in step (3) is 1:1, 5:1, 7:1 or 10:1.

[0066] In some preferred embodiments, in step (4), the ball mill speed is 400 rpm and the grinding time is 48 h to obtain a composite catalyst.

[0067] All raw materials used in the embodiments of the present invention are purchased from the market. Among them, pyrite is purchased from Tongling, Anhui Province.

[0068] The technical solution of the present invention is further illustrated by the following embodiments.

[0069] Example 1

[0070] like Figure 1 As shown, a method for preparing a Pyrite@WS2 self-repairing cyclic catalyst is as follows:

[0071] (1) Pretreatment of pyrite

[0072] After simple grinding, the pyrite was passed through a 300-mesh sieve, and the sieved pyrite was rinsed with deionized water and then dehydrated with anhydrous ethanol, which was repeated three times. Finally, it was placed in a vacuum drying oven, vacuumed and dried at 70°C for 12 hours, taken out and stored in a closed glass drying jar;

[0073] (2) Preparation of Nano-WS2

[0074] Accurately weigh 1.6493g Na2WO4·2H2O, 0.6949g NH2OH·HCl and 1.5224g CH4N2 and dissolve them in 30mL deionized water. After sufficient stirring, add 2mol / L HCl to adjust the pH value of the mixed solution to 6.0. Then transfer the solution to an autoclave equipped with a polytetrafluoroethylene liner; place the autoclave in an electric constant temperature blast drying oven at 180°C and heat for 24h. After the reaction is completed, let the autoclave cool naturally to room temperature, take out the precipitate and place it in a centrifuge tube, and wash it 10 times with distilled water and anhydrous ethanol respectively; after washing, transfer the solid product to a watch glass, vacuum dry it in a vacuum drying oven at 60°C for 10h, then take it out, collect and store it;

[0075] (3) Preparation of Pyrite@WS2

[0076] The pretreated pyrite powder was evenly mixed with WS2 nanosheets in mass ratios of 1:1, 5:1, 7:1 and 10:1, placed in a zirconia ball mill (zirconia grinding ball material ratio was 30) and ground at 400 rpm for 48 hours to obtain composite catalyst samples named Pyrite@WS2(1:1), Pyrite@WS2(5:1), Pyrite@WS2(7:1) and Pyrite@WS2(10:1).

[0077] Figure 2 This is a picture of an actual sample of Pyrite@WS2 (7:1). As can be seen from the picture, it is in a black powder state.

[0078] Figure 3The SEM images of Pyrite@WS2 and pretreated Pyrite prepared under the conditions of pretreated Pyrite: nano WS2 = 7:1 in Example 1 of the present invention; a is pretreated Pyrite; b is Pyrite@WS2 at a scale of 20nm; c is Pyrite@WS2 at a scale of 200nm; the size and morphology of the catalyst material were studied by scanning electron microscopy (SEM). It can be seen from the figure that the sheets in the Pyrite@WS2 composite catalyst sample are very tightly stacked, which is attributed to the presence of the co-catalyst WS2; and the particle stacking phenomenon after loading is more obvious, which may be caused by the mechanical ball milling treatment of the sample and the loading of WS2.

[0079] The phase of the composite catalyst prepared in Example 1 was identified using an X-ray diffractometer.

[0080] The material phase was identified by X-ray diffractometer, and the characterization results are as follows: Figure 3 As shown. The original pyrite shows characteristic diffraction peaks at 2θ of 28.52°, 33.05°, 37.08°, 40.77°, 47.43°, 56.29°, 59.02°, 61.69° and 64.29°, which match the (111), (200), (210), (211), (220), (311), (222), (023) and (321) crystal planes of FeS2 (JCPDS 71-1680), indicating that the main component of the original mineral pyrite is FeS2. In addition, in addition to the characteristic peaks of FeS2, there are also some miscellaneous peaks, which are attributed to the presence of some indispensable impurities and defects in the original mineral. After pyrite and hydrothermally synthesized WS2 were mixed and ball-milled to form a pyrite@WS2 composite material, its diffraction peaks not only retained the pyrite diffraction peaks, but also showed characteristic diffraction peaks at 14.3°, 28.8°, 32.7, 33.5°, 39.5°, 43.8°, 58.4°, 60.5°, 66.5°, 68.6° and 69.1° that perfectly matched WS2 (JCPDS 08-0237).

[0081] Effect verification

[0082] Effect Example 1

[0083] In the catalytic degradation experiment, first weigh a certain amount (the specific ratio of the composite catalyst to the RhB solution is 0.05g:50mL) of the composite catalyst Pyrite@WS2 prepared in Example 1 and place it in a RhB solution of a specific concentration to obtain a mixture. In order to ensure the uniform dispersion of the composite catalyst in the RhB solution, the mixture is treated in an ultrasonic machine for 1 min. The mixture is then transferred to a magnetic stirrer and stirred in the dark for 30 min to promote the full adsorption of RhB molecules on the catalyst surface. Subsequently, H2O2 is injected to a concentration of 4.5mmol / L to induce the Fenton reaction. The absorbance of the sample is measured at specified time intervals using a UV-visible spectrophotometer. The degradation efficiency of RhB is calculated as follows:

[0084] D=[(C0-C t ) / C0]×100%

[0085] Where D is the degradation efficiency of RhB, C0 is the initial concentration, C t is the concentration at time t;

[0086] Note: The optimal conditions in the degradation test are: the mass ratio of pretreated Pyrite to nano WS2 is 7:1; the concentration of pollutants is 20mg / L; the pH value of pollutants is 4 and the concentration of H2O2 is 4.5mmol / L. That is, in the following 1 to 4 effect verifications, except for controlling single factor variables, the parameters and conditions in the other degradation tests are all optimal parameters.

[0087] 1. Comparative Experiments of Different Catalysts

[0088] By comparing the catalytic effects of different catalysts, the optimal composite ratio of the composite catalyst was studied. Figure 5 As shown, the degradation rate of the composite catalyst is better than that of the single-use nano WS2 (obtained in step (2) of Example 1), the pretreated pyrite (obtained in step (1) of this Example 1) and hydrogen peroxide, and Pyrite+WS2 (simple mixing according to the mass ratio of pretreated Pyrite and nano WS2 of 1:1). The degradation rate of the composite catalyst with pretreated Pyrite: nano WS2 = 7:1 is better than that with pretreated Pyrite: nano WS2 = 5:1. This reduction may be due to Fe 2+ The content is insufficient, and H2O2 cannot be fully activated to produce ·OH to degrade pollutants. When the ratio of pretreated Pyrite and nano-WS2 exceeds 7:1, the degradation rate gradually decreases. This reduction may be due to the production of Fe 3+ Excessive Fe bound to the catalyst surface 3+ increases, reducing the available active sites for H2O2 binding.

[0089] 2. Comparative Experiments of Different Pollutant Concentrations

[0090] By simulating wastewater with different concentrations (10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L), the effects of different concentrations of rhodamine B on the degradation effect were studied. Figure 6 As shown in Figure 2, when the RhB concentration exceeds 20 mg / L, the degradation rate decreases with increasing concentration. When the pollutant concentration is 10 mg / L, the reason for the poor degradation effect is that the pollutant molecules are sparsely distributed and the probability of collision with the catalyst is low, resulting in a slow reaction rate. However, as the reaction time increases, degradation gradually occurs. However, when the RhB concentration reaches 30-40 mg / L, the degradation rate gradually decreases. This reduction may be due to the increase in RhB bound to the catalyst surface, which reduces the available active sites for H2O2 binding, thereby inhibiting the generation of OH and reducing the degradation efficiency.

[0091] 3. Comparative experiment of different pH

[0092] The pH value of the pollutants was adjusted between 2 and 10 (2, 4, 6, 8, 10) to study the effect of pH on the degradation efficiency. Figure 7 As shown in Figure 3, the Pyrite@WS2 composite catalyst significantly broadened the applicable pH range. The catalyst can effectively degrade RhB at pH values ​​of 2 to 8. However, when the initial pH exceeded 8, a significant inhibition was observed, which may be due to the deactivation of the catalyst under highly alkaline conditions.

[0093] 4. Cycle number experiment

[0094] According to the optimal conditions for degradation of organic dye pollutants, the pollutant (Rhb) concentration was set to 20 mg / L, the pH value of the pollutant was 4, and the H2O2 concentration was 4.5 mmol / L to explore the degradation cycle number of the composite catalyst Pyrite@WS2 (7:1). Figure 8 As shown, after 5 cycles of experiments, the degradation rate of the pollutant (RhB) can still reach more than 95% within 30 minutes.

[0095] Effect Example 2

[0096] The difference from Example 1 is that the composite catalyst Pyrite@WS2 (7:1) prepared in Example 1 is used to verify the degradation effect of methylene blue, methyl orange, rhodamine B or the mixed pollutants of the three (such as Fig. 9 Other degradation conditions were the same.

[0097] In summary, in the heterogeneous Fenton catalytic reaction, Fe 3+ Converted to Fe 2+is the main rate-limiting step of the reaction. 4+ Increased Fe 3+ Converted to Fe 2+ The rate at which W is generated 6+ Can be further reduced to W by reaction with H2O2 4+ , established Fe 3+ / Fe 2+ and W 6+ / W 4+ The double-circulation system (the specific reaction mechanism is as follows). In addition, under acidic conditions, the catalyst surface contains abundant sulfur vacancies, which serve as reaction sites and promote the adsorption of pollutants on the catalyst surface. The accumulation of such pollutants near the active sites increases the degradation rate. Unlike simple physical mixing, the tightly bound Pyrite@WS2 composite catalyst achieves fast and direct electron transfer due to the existence of heterojunction bonds endowed by mechanochemical energy, further accelerating the Fe 3+ / Fe 2+ Cycle process. In summary, the exposed W 4+ The presence of sulfur vacancies and heterojunction bonds between catalyst components effectively enhances the degradation rate of RhB.

[0098] Fe 2+ +H2O2→Fe 3+ + OH+OH - (1)

[0099] Fe 3+ +H2O2→Fe 2+ +·OOH+H + (2)

[0100] Fe 3+ +·OOH→Fe 2+ +O2+H + (3)

[0101] W 4+ +Fe 3+ →Fe 2+ +W 6+ (4)

[0102] W 6+ +H2O2→W 4+ +H2O+O2(5)

[0103] From the above effect test, it can be seen that the present invention provides a pyrite@WS2 heterogeneous Fenton reagent, in which pyrite is modified by WS2 and introduced into the catalyst to improve the catalytic efficiency. According to the effect test, it can be seen that the composite catalyst disclosed in the present invention can effectively degrade organic wastewater. After 5 consecutive cycles of reaction, the removal rate of rhodamine B can be maintained at more than 95%; and the catalyst exhibits excellent stability and catalytic activity in a variety of pH environments, significantly reducing secondary pollution and improving reaction efficiency.

[0104] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst, characterized in that: The following steps are involved: Nano-WS2 and pre-treated pyrite were mechanochemically ball-milled to prepare pyrite@WS2; Wherein, the mass ratio of the pretreated pyrite to the nano WS2 is (1-10):

1.

2. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 1, characterized in that: The mass ratio of the pretreated pyrite to the nano-WS2 is 7:

1.

3. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 1, characterized in that: During the mechanochemical ball milling process, the ball milling speed is 300-500 rpm, and the ball milling time is 24-48 hours.

4. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 1, characterized in that: The preparation process of the nano WS2 is as follows: Dissolve Na2WO4·2H2O, NH2OH·HCl and CH4N2S in water to obtain a mixed solution; The mixed solution is first heated at a constant temperature, and then cooled to room temperature after the reaction is complete.

5. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 4, characterized in that: The usage ratio of Na2WO4·2H2O, NH2OH·HCl, CH4N2S and water is: (1.5-1.7) g: (0.6-0.7) g: (1.4-1.6) g: 30 mL.

6. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 4, characterized in that: The heating temperature in the constant temperature heating process is 180° C. and the heating time is 24 hours.

7. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 4, characterized in that: After cooling to room temperature, the precipitate needs to be taken out, washed and dried; The conditions in the drying process are: drying at 60° C. and vacuum conditions for 10 hours.

8. The method for preparing a pyrite@WS2 heterogeneous Fenton composite catalyst according to claim 1, characterized in that: The pretreatment method of pyrite is as follows: wash the pyrite three times and dry it at 70°C under vacuum for 12 hours.

9. A pyrite@WS2 heterogeneous Fenton composite catalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the pyrite@WS2 heterogeneous Fenton composite catalyst as claimed in claim 9 in catalytic degradation of organic dye pollutants in sewage, characterized in that: The organic dye pollutants include methylene blue, methyl orange and rhodamine B.

Citation Information

Cited By

  • Preparation method and application of pyrite carbon nitride composite material

    CN120920044A